Catalytic cracking of palm oil over zeolite catalysts: Statistical approach - Twaiq, F. A. A.; Bhatia, S. (IIUM Press, International Islamic University Malaysia, 2001)

(untitled)
The catalytic cracking of palm oil was conducted in a fixed bed micro-reactor over HZSM-5, zeolite  and ultrastable Y (USY) zeolite catalysts. The objective of the present investigation was to study the effect of cracking reaction variables such as temperature, weight hourly space velocity, catalyst pore size and type of palm oil feed of different molecular weight on the conversion, yield of hydrocarbons in gasoline boiling range and BTX aromatics in the organic liquid product. Statistical Design of Experiment (DOE) with 24 full factorial design was used in experimentation at the first stage. The nonlinear model and Response Surface Methodology (RSM) were utilized in the second stage of experimentation to obtain the optimum values of the variables for maximum yields of hydrocarbons in gasoline boiling range and aromatics. The HZSM-5 showed the best performance amongst the three catalysts tested. At 623 K and WHSV of 1 h-1, the highest experimental yields of gasoline and aromatics were 28.3 wt.% and 27 wt.%, respectively over the HZSM-5 catalyst. For the same catalyst, the statistical model predicted that the optimum yield of gasoline was 28.1 wt.% at WHSV of 1.75 h-1 and 623 K. The predicted optimum yield of gasoline was 25.5 wt.% at 623 K and WHSV of 1 h-1.